Field Philosophy as a Disturbing Practice: Philosophical Legitimacy and Methodological Divergence - Nyamike, Adou Josias (European Scientific Journal, ESJ, 2026)
This article examines field philosophy as an emerging practice within the humanities in a context shaped by increasing demands for social relevance and public contributions of publicly funded research. It argues that field philosophy is neither a simple application of philosophical theories to concrete situations nor an imitation of objectifying social science methods. Rather, it should be understood as an autonomous, though marginalized, philosophical practice grounded in a reflexive stance, the co-construction of questioning, and attention to how ideas are appropriated by actors in practice settings. Drawing on a cross reading of Frodeman, Vollaire, Despret, Buchanan, and Stengers, the article develops two complementary lines of analysis. First, it clarifies the conditions under which field philosophy can claim philosophical legitimacy, showing how disciplinary norms and institutional routines can exclude situated and transdisciplinary approaches. Second, it specifies both the proximities and the differences between field philosophy and empirical social sciences. While both attend to situated experience, field philosophy is distinguished by its aim to transform meaning, by an ethics of dialogical equality, and by an emphasis on post-research follow-up as an indicator of durability and actor empowerment. The article concludes that field philosophy should be recognized as a generative, relational, and transformational practice capable of shifting conventional criteria of philosophical validity while renewing the social responsibility of philosophical work.